The Use of Botanical Preservatives to Maintain the Quality of Smoked Catfish - Edo Saputra; Rokhani Hasbullah; Emmy Darmawati; Mala Nurilmala (The University of Lampung, 2026)
The use of botanical preservatives in smoked catfish is a natural approach to maintaining quality during initial storage through the antioxidant and antimicrobial activities of its bioactive compounds. This study aims to examine the effect of garlic, red ginger, and red galangal extracts in maintaining the sensory quality, color stability, and microbiological contamination of smoked catfish. Smoked catfish were coated with botanical extracts according to the formulation, then stored at room temperature and evaluated after five days of storage. The parameters observed included color changes, sensory evaluation, and microbial contamination. The data were analyzed using ANOVA, Pearson's correlation, and quadratic regression models to identify the relationship between treatment and quality response. The results showed that botanical preservatives were significantly (p < 0.05) effective in slowing the deterioration of smoked catfish quality. The preservative formulation of 25% garlic, 50% red ginger, and 25% red galangal was the best treatment, with better color stability, improved sensory acceptance, and a more effective mechanism of inhibiting microbial growth. These findings confirm the potential of botanical preservatives as a natural preservative alternative for smoked catfish products.